Driving Forces to Implement Industry 4.0 in Manufacturing SMES - Anna KWIOTKOWSKA (Communications of International Proceedings, 2021)
The fourth industrial revolution - also named Industry 4.0 - is becoming increasingly popular around the world and its huge innovation potential and intensive use of advanced technologies is affecting various kinds of sectors, especially the manufacturing sector. However, researches on the opinions of companies, especially SMEs implementing Industry 4.0 solutions are still insufficient. The primary objective of the article is therefore to fill the cognitive gap by analyzing the opinions of managers on the most important driving forces relevant to the implementation of Industry 4.0 solutions. This paper applied a qualitative case study design involving 34 semi-structured interviews with leading high-level managers, including chief digital officers and chief executive officers from Polish manufacturing SMEs. The study also used company websites and annual reports, as well as a defined research protocol using company visits and interviews. The results identified five main groups related to market conditions, human and financial resources, management, productivity and efficiency as the main drivers of the implementation of Industry 4.0. The results of the research can be used by scientists and managers to develop strategic plans, as well as to conduct further research on the implementation processes of Industry 4.0 in Poland.
Keywords: Drivers; manufacturing SMEs; Industry 4.0